Persistence of inflammatory and vascular mediators 5 months after hospitalization with COVID-19 infection - Melhorn, J; Alamoudi, A; Mentzer, AJ; Fraser, E; Fries, A; Cassar, MP; Kwok, A; Knight, JC; Raman, B; Talbot, NP; Petousi, N (Frontiers Media, 2023)
Background and aim: In acute severe COVID-19, patients present with lung inflammation and vascular injury, accompanied by an exaggerated cytokine response. In this study, our aim was to describe the inflammatory and vascular mediator profiles in patients who were previously hospitalized with COVID-19 pneumonitis, months after their recovery, and compare them with those in patients recovering from severe sepsis and in healthy controls.